Therapeutic Potential of Nutraceuticals and Dietary Supplements in the Prevention of Viral Diseases: A Review - Singh, Saumya; Kola, Prithwish; Kaur, Dalveer; Singla, Gisha; Mishra, Vibhu; Panesar, Parmjit S.; Mallikarjunan, Kumar; Krishania, Meena (Frontiers in Nutrition, 2021)
Presently, viral diseases are a leading concern of morbidity worldwide and despite enormous scientific advances, their potential to spread is escalating, and eventually into pandemics. Nutrition can play a major role in supporting the immune system of the body, and for optimal functioning of the cells of the immune system. Healthy diet encompassing vitamins, multi-nutrient supplements, functional foods, nutraceuticals and probiotics can play a pivotal role in combating several viral invasions besides strengthening the immune system. This review provides comprehensive information on diet based scientific recommendations, evidence and worldwide case studies in light of current pandemic and also with particular focus on virus-induced respiratory tract infections. After reviewing the immune potential of nutraceuticals based on studies in labs and humans it was concluded that bioactive compounds as nutraceuticals, vitamins and functional foods such as honey, berries etc, with proven anti viral efficacy, in addition to pharmaceutical medication or alone, can prove instrumental in treating a range of virus induced infections, besides strengthening the immune system. Milk proteins and peptides can also act as adjuvants for the design of more potent novel antiviral drugs.